Management of Rumah Atsiri Indonesia Educational Tourism During the COVID-19 Pandemic - Mustofa, Rochman Hadi; Isnanto, Taufik (Journal of Indonesian Tourism and Development Studies, 2024)
The COVID-19 pandemic has caused a significant impact, especially on the tourism industry. This study aimed to explore the management strategy of tourism education at the Indonesian Atsiri House during the COVID-19 pandemic, along with the challenges encountered by the management and the effective measures implemented to overcome them. This study employs a qualitative case study method to examine the management strategy of tourism education at the Indonesian Atsiri House during the pandemic. The research methodology involves interviews, documentation analysis, and field observations. Key informants included the executive secretary, marketing division, tour guides, and tourists. Based on the analysis results, Indonesian Atsiri House effectively managed the challenges posed by the pandemic. Adequate facilities, adherence to government health protocols, and strategies focused on hygiene and health information, while medium-term strategies involved collaborating with various media platforms to promote Atsiri House. Long-term strategies included the renovation of tourist destinations and supporting facilities. This study described management and marketing strategies that could be used to reference other similar educational tours. Keywords: Atsiri House, COVID-19, Educational Tourism, Tourism Management, Virtual Tour.